Is Cardioprotection Dead?. Issue 1 (4th July 2017) - Lefer, David J.; Marbán, Eduardo
Abstract : For >4 decades, the holy grail in the treatment of acute myocardial infarction has been the mitigation of lethal injury. Despite promising initial results and decades of investigation by the cardiology research community, the only treatment with proven efficacy is early reperfusion of the occluded coronary artery. The remarkable record of failure has led us and others to wonder if cardioprotection is dead. The path to translation, like the ascent to Everest, is certainly littered with corpses. We do, however, highlight a therapeutic principle that provides a glimmer of hope: cellular postconditioning. Administration of cardiosphere-derived cells after reperfusion limits infarct size measured acutely, while providing long-term structural and functional benefits. The recognition that cell therapy may be cardioprotective, and not just regenerative, merits further exploration before we abandon the pursuit entirely.